The right tools for the job : (Palgrave Macmillan, 2005)
This book is the result of a four-year study into the most commonly used management tools and techniques in the areas of business strategy and finance, marketing, production and operations, and procurement and supply chain management. It explains which tools are used in small, medium-sized and large companies, whether based in the US, Europe or Asia, across many different industrial and service sectors. It explains where companies find out about particular tools, and examines which appear to be the most successful.